2010
DOI: 10.1111/j.1559-1816.2010.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for Health‐Related Physical Activity

Abstract: Tenets of Weiner's (1985, 1986) attribution theory were examined in the context of being active enough for health benefits, including associations between attributions, emotions, and future expectations. Participants completed questionnaires assessing activity, perceived success/failure to be active enough for health benefits, attributions, emotions, and future expectancy. Perception of being active enough for health benefits was associated with more internal, personally controllable, and stable attributions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A similar protocol has been successfully used previously to assess perceived activity outcomes (Nickel & Spink, 2010b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar protocol has been successfully used previously to assess perceived activity outcomes (Nickel & Spink, 2010b).…”
Section: Methodsmentioning
confidence: 99%
“…These include stability (belief that the cause is permanent vs. temporary), locus of causality (belief that the individual vs. the situation is responsible), and controllability (belief that the cause is controllable vs. uncontrollable). Weiner predicted that the stability of attributions would be the most important in determining future expectations (Weiner, 1986), and previous research concerning health-related physical activity has supported the role of stability in predicting certainty of similar future outcomes (Nickel & Spink, 2010b). Self-efficacy and future expectations are not synonymous, but they are related (Bandura, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…There is good support for a relationship between team attributions and self-esteem in team sport (Green & Holman, 2004;Sherman & Kim, 2005;Sherman, Kinias, Major, Kim, & Prenovost, 2007) and several experimental studies have demonstrated that a greater use of team-serving attributions causes subsequent increases in social self-esteem (Smurda et al, 2006). A related emotion, pride, has also been assessed in attribution research (Tracy & Robins, 2007;Nickel & Spink, 2010). Both pride and self-esteem should respond similarly to attributions, and controllability in particular has been hypothesised have an important effect on these feeling states (Goetz, Frenzel, Stoeger, & Hall, 2010).…”
Section: Affective Consequencesmentioning
confidence: 99%
“…Personal control refers to the ability of the person to control the primary cause (controllable or uncontrollable), while external control refers to the ability of others to control the primary cause (controllable or uncontrollable). The external control dimension has been excluded from previous research on attributions for PA and may not be useful here as these types of attributions cannot be self-regulated (Minifee & McAuley, 1998;Nickel & Spink, 2010). Therefore, the external control dimension was measured, but there are no hypothesized results for this dimension.…”
Section: Attributions the Attributions Measurement Used Was The Causmentioning
confidence: 99%
“…More internal, stable, and personally controllable attributions (e.g., long term effort) lead to higher frequency and higher perceived success of PA (Minifee & McAuley, 1998;Nickel & Spink, 2010). Individuals with a lower frequency of PA behavior and individuals who failed to adhere to an exercise program make less internal, more unstable, and more personally uncontrollable attributions (Minifee & McAuley, 1998).…”
Section: Attribution Theorymentioning
confidence: 99%